BiVO4 / TiC composite photoelectric catalyst as well as preparation method and application thereof
By introducing TiC into the BiVO4 photoelectric catalyst, the BiVO4/TiC composite photoelectric catalyst is formed, and the problems of charge recombination and light absorption range of BiVO4 photoelectric catalyst are solved, efficient photoelectric conversion and oxygen evolution efficiency are achieved, and the preparation process is simplified and the cost is reduced.
Patent Information
- Application Number
- CN202411884813.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing BiVO4 photoelectric catalysts have charge recombination problems, limited light absorption range, low photoelectric conversion efficiency and oxygen evolution efficiency, and complex preparation process and high cost.
TiC with small size and large specific surface area was prepared by sintering method, and BiVO4 powder with high purity and good crystallinity was prepared by low-temperature water bath method to form BiVO4/TiC composite photoelectric catalyst. This method enhances the separation and transmission of photogenerated charges through heterostructure, broadens the light absorption range, and improves photoelectric conversion efficiency and oxygen evolution efficiency.
It has achieved the reduction of charge recombination, widens the light absorption range, improves the photoelectric conversion efficiency and oxygen evolution efficiency, and has a simple preparation process, easy control conditions, and low cost, which is suitable for industrial production.
Smart Images

Figure CN119753738A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of functional materials, relates to photoelectrocatalytic materials, and specifically relates to a BiVO4 / TiC composite photoelectrocatalyst and a preparation method and application thereof. Background Art
[0002] Due to economic development and resource shortage, people are in urgent need of developing new renewable energy sources to solve the current energy shortage problem. Photoelectrochemical (PEC) water splitting is considered to be one of the most promising strategies for human society to solve environmental and energy problems in the future. Under sunlight, semiconductor photoelectrodes generate photogenerated electrons and holes to produce hydrogen and oxygen from water splitting, respectively. In order to withstand oxidative conditions and maintain long-term stability in aqueous solution, oxide semiconductors (such as TiO2, ZnO, BiVO4 and WO3) have become the preferred photoelectrode candidates. Among these materials, BiVO4 has received great attention as a photoanode for photoelectrochemical water splitting due to its suitable band structure and excellent semiconductor properties. The monoclinic phase of BiVO4 is an n-type semiconductor, and its valence band is dominated by the 6s and 2p orbitals of Bi and O, respectively. The band gap energy of this material is between 2.4-2.5eV, so it is suitable for absorbing sunlight. Therefore, BiVO4 is an ideal photoanode. Compared with many other metal oxides, it can evolve oxygen at low bias voltage. However, due to its short hole migration distance and weak electron migration ability, the photocatalytic efficiency is affected.
[0003] Transition metal carbides (TMCs) consist of non-precious transition metals and have been known for their "Pt-like behavior" since 1973. Titanium carbide is a typical transition metal carbide and is a promising material due to its high tolerance to acids and bases. Its high melting point, high hardness, excellent elastic modulus, good conductivity, low density, etc. have attracted a large number of scholars to explore low-cost and high-activity synthesis methods of titanium carbide. However, the number of active sites on the surface of TiC is limited, and the charge transfer efficiency is low, which limits its electrocatalytic performance. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a BiVO4 / TiC composite photoelectric catalyst and its preparation method and application. The catalyst can reduce charge recombination, broaden the light absorption range, improve the photoelectric conversion efficiency, and improve the oxygen evolution efficiency. The preparation process is simple, the conditions are easy to control, and the cost is low.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A method for preparing a BiVO4 / TiC composite photoelectric catalyst comprises the following steps:
[0007] Step 1: Put titanium dioxide and carbon black powder into a mortar in a mass ratio of (0.5-2): (1-3), grind and mix thoroughly, transfer to a white porcelain boat, and place in a muffle furnace. In an argon Ar atmosphere, heat to 1400-1600° C. at a heating rate of 5-15° C. / min, calcine for 2-6 hours, and then cool naturally to room temperature with the furnace. Take out the sample and grind it to obtain black powder A, which is TiC powder.
[0008] Step 2: dissolve 0.1-2 mmol bismuth nitrate pentahydrate in 50-100 mL of 0.5 mol / L HNO3 solution, and dissolve 0.1-2 mmol NH4VO3 in 50-100 mL of 1.0 mol / L NaOH solution, mix the two solutions under vigorous stirring to form a yellow solution, and then place the solution under a magnetic stirrer and stir for 1 hour to obtain precursor solution A;
[0009] Step 3: Transfer the precursor A to a water bath, set the water bath to 60-100°C, keep warm for 6-10 hours, then add 0.1-1g TiC powder; heat the water bath to 80-120°C for a second time, continue heating for 2-4 hours, centrifuge the reacted solution to remove the supernatant to obtain a precipitate, then wash, dry and grind to obtain the desired BiVO4 / TiC composite photoelectric catalyst.
[0010] Preferably, the grinding in step 1 and step 3 is to grind the sample in a mortar for 30 to 90 minutes.
[0011] Preferably, the centrifugation in step three is performed at 8000-12000 r / min for 5-15 min.
[0012] Preferably, the washing in step three is performed by alternately rinsing with deionized water and anhydrous ethanol for 3 to 5 times.
[0013] Preferably, the drying in step three is to place the product in a vacuum drying oven at 80° C. and dry it for 8 to 16 hours.
[0014] The present invention also protects a BiVO4 / TiC composite photoelectric catalyst prepared by the method as described above and its application as a photoanode in the process of photoelectric catalytic water decomposition.
[0015] Compared with the prior art, the present invention has the following technical effects:
[0016] The present invention firstly adopts a sintering method to prepare TiC with a small size and a large specific surface area, and further prepares BiVO4 powder with high purity and good crystallinity by a low-temperature water bath method. TiC has good electrical conductivity, can promote the separation and transmission of photogenerated charges, reduce charge recombination, improve photoelectric conversion efficiency, and enhance the stability of the composite material. BiVO4 has good absorption capacity for visible light, which helps to improve the utilization efficiency of solar energy. The combination of the two to form a heterogeneous structure can enhance the efficient separation and transmission of photogenerated charges, improve the utilization rate of sunlight, and thus achieve the improvement of oxygen evolution efficiency.
[0017] The preparation process of the invention is simple, the reaction conditions are mild and controllable, the production cost is low, and it is easy to industrialize the production. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the X-ray diffraction analysis diagram of BiVO4 / TiC prepared in Example 2;
[0019] Figure 2 This is a scanning electron microscope image of the BiVO4 / TiC photoelectrocatalyst prepared in Example 2 at 2 um;
[0020] Figure 3 This is a graph showing the oxygen evolution performance of BiVO4 / TiC prepared in Example 2 and pure phase TiC in a solution with a pH of 9.5. DETAILED DESCRIPTION
[0021] The specific contents of the present invention are further explained in detail below in conjunction with the examples. The reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art. The test methods in the following examples where specific experimental conditions are not specified are usually based on conventional experimental conditions. Unless otherwise specified, the reagents and raw materials used in the present invention can be obtained commercially.
[0022] Embodiment 1:
[0023] This embodiment provides a method for preparing a BiVO4 / TiC composite photoelectric catalyst, comprising the following steps:
[0024] Step 1: Put titanium dioxide and carbon black powder into a mortar in a mass ratio of 0.5:1, grind for 30 minutes until fully mixed, transfer to a white porcelain boat, and place it in a muffle furnace. In an argon Ar atmosphere, heat the temperature to 1400°C at a rate of 5°C / min, calcine for 2 hours, and then naturally cool to room temperature with the furnace. Take out the sample and grind it for 30 minutes to obtain black powder A, which is TiC powder;
[0025] Step 2: Dissolve 0.1 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) in 50 mL of 0.5 mol / L HNO3 solution, and simultaneously dissolve 0.1 mmol of NH4VO3 in 50 mL of 1.0 mol / L NaOH solution. Mix the two solutions under vigorous stirring to form a yellow solution, and then stir the solution under a magnetic stirrer for 1 h to obtain precursor solution A.
[0026] Step 3: Transfer the precursor A to a water bath, set the water bath to 60°C, keep warm for 6 hours, then add 0.1g TiC powder; heat the water bath to 80°C for the second time, continue heating for 2 hours, pour the reacted solution into a centrifuge tube, centrifuge at 8000r / min for 5 minutes, remove the supernatant, and obtain a precipitate. Rinse it three times with deionized water and anhydrous ethanol alternately, place the product in a vacuum drying oven at 80°C and dry it for 8 hours, take it out and grind it for 30 minutes until it is uniform to obtain the desired BiVO4 / TiC composite photoelectric catalyst;
[0027] The chi660e equipment was used to test the photoelectrocatalytic effect of BiVO4 / TiC composite photoelectrocatalyst.
[0028] Embodiment 2:
[0029] Step 1: Put titanium dioxide and carbon black powder into a mortar in a mass ratio of 1:2, grind for 60 minutes until fully mixed, transfer to a white porcelain boat, and place it in a muffle furnace. In an argon Ar atmosphere, heat the temperature to 1500°C at a rate of 10°C / min, calcine for 4 hours, and then naturally cool to room temperature with the furnace. Take out the sample and grind for 60 minutes to obtain black powder A, which is TiC powder;
[0030] Step 2: Dissolve 1 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) in 80 mL of 0.5 mol / L HNO3 solution, and simultaneously dissolve 1 mmol of NH4VO3 in 80 mL of 1.0 mol / L NaOH solution. Mix the two solutions under vigorous stirring to form a yellow solution, and then stir the solution under a magnetic stirrer for 1 h to obtain precursor solution A.
[0031] Step 3: Transfer the precursor A to a water bath, set the water bath to 80°C, keep warm for 8 hours, then add 0.5g TiC powder; heat the water bath to 100°C for the second time, continue heating for 3 hours, pour the reacted solution into a centrifuge tube, centrifuge at 10000r / min for 10 minutes, remove the supernatant, and obtain a precipitate. Rinse it alternately with deionized water and anhydrous ethanol three times, place the product in a vacuum drying oven at 80°C and dry it for 12 hours, take it out and grind it for 60 minutes until it is uniform to obtain the desired BiVO4 / TiC composite photoelectric catalyst;
[0032] The chi660e equipment was used to test the photoelectrocatalytic effect of BiVO4 / TiC composite photoelectrocatalyst.
[0033] Figure 1 This is the X-ray diffraction analysis diagram of BiVO4 / TiC prepared in Example 2, where the horizontal axis is the 2θ angle and the vertical axis is the diffraction peak intensity. The composite phase powder can accurately correspond to the BiVO4 PDF#14-0688 card and the TiC PDF#32-1383 card, indicating that the BiVO4 powder and the TiC powder are successfully composited;
[0034] Figure 2 This is a scanning electron microscope image of the BiVO4 / TiC photoelectrocatalyst prepared in Example 2 at 2 um. It can be seen from the image that the bulk TiC is attached to the flaky BiVO4, which indicates that BiVO4 and TiC are successfully composited;
[0035] Figure 3 The oxygen evolution performance of BiVO4 / TiC and pure phase TiC prepared in Example 2 in a solution with a pH of 9.5 is shown in the figure. It can be seen from the figure that the pure phase TiC photoelectrocatalyst exhibits 0.68 mA / cm at 1.23 V. 2 The current density of BiVO4 / TiC composite photocatalyst was 1.57 mA / cm at 1.23 V. 2 The current density is 2.3 times higher than that of pure phase TiC photoelectrocatalyst.
[0036] Embodiment 3:
[0037] Step 1: Put titanium dioxide and carbon black powder into a mortar in a mass ratio of 2:3, grind for 90 minutes until fully mixed, transfer to a white porcelain boat, and place it in a muffle furnace. In an argon Ar atmosphere, heat the temperature to 1600°C at a rate of 15°C / min, calcine for 2 hours, and then naturally cool to room temperature with the furnace. Take out the sample and grind it for 90 minutes to obtain black powder A, which is TiC powder;
[0038] Step 2: Dissolve 2 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) in 100 mL of 0.5 mol / L HNO3 solution, and simultaneously dissolve 2 mmol of NH4VO3 in 100 mL of 1.0 mol / L NaOH solution. Mix the two solutions under vigorous stirring to form a yellow solution, and then place the solution under a magnetic stirrer and stir for 1 h to obtain precursor solution A.
[0039] Step 3: Transfer the precursor A to a water bath, set the water bath to 100°C, keep warm for 8 hours, then add 1g of TiC powder; heat the water bath to 120°C for the second time, continue heating for 3 hours, pour the reacted solution into a centrifuge tube, centrifuge at 12000r / min for 5 minutes, remove the supernatant, and obtain a precipitate. Rinse it four times with deionized water and anhydrous ethanol alternately, place the product in a vacuum drying oven at 80°C and dry it for 16 hours, take it out and grind it for 90 minutes until it is uniform to obtain the desired BiVO4 / TiC composite photoelectric catalyst;
[0040] The chi660e equipment was used to test the photoelectrocatalytic effect of BiVO4 / TiC composite photoelectrocatalyst.
[0041] Embodiment 4:
[0042] Step 1: Put titanium dioxide and carbon black powder into a mortar in a mass ratio of 0.5:3, grind for 90 minutes until fully mixed, transfer to a white porcelain boat, and place it in a muffle furnace. In an argon Ar atmosphere, heat the temperature to 1400°C at a rate of 15°C / min, calcine for 6 hours, and then naturally cool to room temperature with the furnace. Take out the sample and grind it for 90 minutes to obtain black powder A, which is TiC powder;
[0043] Step 2: Dissolve 0.5 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) in 100 mL of 0.5 mol / L HNO3 solution, and dissolve 1 mmol of NH4VO3 in 100 mL of 1.0 mol / L NaOH solution. Mix the two solutions under vigorous stirring to form a yellow solution, and then stir the solution under a magnetic stirrer for 1 h to obtain precursor solution A.
[0044] Step 3: Transfer the precursor A to a water bath, set the water bath to 60°C, keep warm for 10 hours, then add 1g of TiC powder; heat the water bath to 120°C for the second time, continue heating for 4 hours, pour the reacted solution into a centrifuge tube, centrifuge at 8000r / min for 15 minutes, remove the supernatant, and obtain a precipitate. Rinse it three times with deionized water and anhydrous ethanol alternately, place the product in a vacuum drying oven at 80°C and dry it for 16 hours, take it out and grind it for 90 minutes until it is uniform to obtain the desired BiVO4 / TiC composite photoelectric catalyst;
[0045] The chi660e equipment was used to test the photoelectrocatalytic effect of BiVO4 / TiC composite photoelectrocatalyst.
[0046] Embodiment 5:
[0047] Step 1: Put titanium dioxide and carbon black powder in a mortar in a mass ratio of 1:1, grind for 90 minutes until fully mixed, transfer to a white porcelain boat, and place it in a muffle furnace. In an argon Ar atmosphere, heat the temperature to 1600°C at a rate of 15°C / min, calcine for 2 hours, and then naturally cool to room temperature with the furnace. Take out the sample and grind it for 90 minutes to obtain black powder A, which is TiC powder;
[0048] Step 2: Dissolve 2 mmol of bismuth nitrate pentahydrate (Bi(NO3)3·5H2O) in 100 mL of 0.5 mol / L HNO3 solution, and simultaneously dissolve 1.5 mmol of NH4VO3 in 100 mL of 1.0 mol / L NaOH solution. Mix the two solutions under vigorous stirring to form a yellow solution, and then place the solution under a magnetic stirrer and stir for 1 h to obtain precursor solution A.
[0049] Step 3: Transfer the precursor A to a water bath, set the water bath to 80°C, keep warm for 8 hours, then add 0.8g TiC powder; heat the water bath to 120°C for the second time, continue heating for 3 hours, pour the reacted solution into a centrifuge tube, centrifuge at 1000r / min for 10 minutes, remove the supernatant, and obtain a precipitate. Rinse it alternately with deionized water and anhydrous ethanol five times, place the product in a vacuum drying oven at 80°C and dry it for 16 hours, take it out and grind it for 90 minutes until it is uniform to obtain the desired BiVO4 / TiC composite photoelectric catalyst;
[0050] The chi660e equipment was used to test the photoelectrocatalytic effect of BiVO4 / TiC composite photoelectrocatalyst.
[0051] It should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it; without departing from the concept of the present invention, the deduction or replacement made by those skilled in the art shall fall within the protection scope of the present invention.
Claims
1. A method for preparing a BiVO4 / TiC composite photoelectrocatalyst, characterized in that: The following steps are involved: Step 1: Put titanium dioxide and carbon black powder into a mortar in a mass ratio of (0.5-2): (1-3), grind until fully mixed, transfer to a white porcelain boat, and place it in a muffle furnace. In an argon Ar atmosphere, heat the boat to 1400-1600° C. at a heating rate of 5-15° C. / min, calcine for 2-6 hours, and then cool naturally to room temperature with the furnace. Take out the sample and grind it to obtain black powder A, which is TiC powder. Step 2: dissolve 0.1-2 mmol bismuth nitrate pentahydrate in 50-100 mL of 0.5 mol / L HNO3 solution, and dissolve 0.1-2 mmol NH4VO3 in 50-100 mL of 1.0 mol / L NaOH solution, mix the two solutions under vigorous stirring to form a yellow solution, and then place the solution under a magnetic stirrer and stir for 1 hour to obtain precursor solution A; Step 3: Transfer the precursor A to a water bath, set the water bath to 60-100°C, keep warm for 6-10 hours, then add 0.1-1g TiC powder; heat the water bath to 80-120°C for a second time, continue heating for 2-4 hours, centrifuge the reacted solution to remove the supernatant to obtain a precipitate, then wash, dry and grind to obtain the desired BiVO4 / TiC composite photoelectric catalyst.
2. The method for preparing the BiVO4 / TiC composite photoelectrocatalyst according to claim 1, characterized in that: The grinding described in step 1 and step 3 is to grind the sample in a mortar for 30 to 90 minutes.
3. The method for preparing the BiVO4 / TiC composite photoelectrocatalyst according to claim 1, characterized in that: The centrifugation described in step 3 is performed at 8000-12000 r / min for 5-15 min.
4. The method for preparing the BiVO4 / TiC composite photoelectrocatalyst according to claim 1, characterized in that: The washing described in step 3 is to rinse with deionized water and anhydrous ethanol alternately 3 to 5 times.
5. The method for preparing the BiVO4 / TiC composite photoelectrocatalyst according to claim 1, characterized in that: The drying described in step 3 is to place the product in a vacuum drying oven at 80° C. and dry it for 8 to 16 hours.
6. A BiVO4 / TiC composite photoelectric catalyst prepared by the method according to any one of claims 1 to 5.
7. Use of the BiVO4 / TiC composite photoelectrocatalyst as claimed in claim 6 as a photoanode in the process of photoelectrocatalytic water decomposition.
Citation Information
Patent Citations
V4C3 MXene-coated BiVO4 photo-thermal catalytic material as well as preparation method and application thereof
CN116899601A
Efficient BiVO4 / Mo2C composite photoelectric catalytic material as well as preparation method and application thereof
CN117987876A